LEGAL PROTECTION OF PATIENTS' RIGHTS AS CONSUMERS IN THE FIELD OF MEDICAL SERVICES AT PERTAMINA HOSPITAL PANGKALAN BRANDAN - Ardian Abdillah Harahap; Tamaulina Sembiring; Sumarno, Sumarno (International Journal of Synergy in Law, Criminal, and Justice, 2024)
This study aims to analyze the effectiveness of legal protection of patient rights as consumers at Pertamina Hospital Pangkalan Brandan, by examining the implementation of Law Number 8 of 1999 concerning Consumer Protection and Law Number 17 of 2023 concerning Health. This study uses a qualitative approach to deepen understanding of the realization of patient rights in medical practice, especially related to the informed consent process and the standards of service provided. The results of the study indicate a significant gap between existing legal regulations and practices in the field, especially in the implementation of informed consent and the consistency of the application of medical service standards. These findings emphasize the importance of improving communication mechanisms between doctors and patients and the need for more effective internal audits. Recommendations put forward include improving staff training and stricter supervision of the implementation of health protocols to ensure consistent fulfillment of patient rights. This study contributes to the literature on consumer protection in health services and strengthens the urgency of policy reform in health facilities.